Identificación del ácaro Varroa destructor y el hongo Ascosphaera apis; patógenos causantes de enfermedades de impacto en apicultura con Apis mellifera en los municipios de Cajibío y Popayán, en el departamento del Cauca. (2023)
The presence of pathogenic microorganisms, such as fungi and ectoparasites, negatively affects the production and reproduction of bees (Apis mellifera), causing economic losses in rural beekeeping; this causes environmental imbalances due to its role as a pollinating agent and other ecological processes. The main objective of the study is to analyze the levels of infestation (Varroa destructor) and evaluate the presence of (Ascosphaera Apis) in the health and production of hives in the municipalities of Cajibío and Popayán - Cauca. The study adopts a descriptive and exploratory approach, where 10 beekeeping farms were sampled, collecting 2 hives per farm, likewise, the alcohol wash test is carried out to evaluate the varroa infestation, and the sowing method and media preparation, to identify Ascosphaera Apis in limed or plastered brood. The infestation rate registered for the municipality of Cajibío is 5.76%, and in Popayán it is 6.76%. When analyzing all the samples in search of spores belonging to (Ascosphaera Apis), the presence is not observed in any of the samples exposed to the sampling protocol.